Vocabulary Learning Strategies Used by Saudi Female EFL Learners - Alzahrani, Kholoud; Alq, Naif (International Journal of Linguistics and Translation Studies, 2023)
The present study aimed at investigating vocabulary learning strategies (VLSs) applied by ten adult female EFL learners at Taif University, Saudi Arabia. In addition, it explored how the current widespread of internet-assisted tools have influenced vocabulary learning strategies and how participants treat new words after encountering them. The data of this study consists of a mixed-methods approach. First, introspective and retrospective verbal reports of ten English-major learners who met new vocabulary while reading a passage. Secondly, in the interview stage, participants were asked about how the internet and mobile resources affect how they approach new words and their lexical knowledge/size. Furthermore, they were asked if they follow specific strategies to commit new vocabulary to memory. The findings of this research showed that the participants used similar vocabulary learning strategies. During the reading task, the most preferred strategy was guessing the meaning of the words from the context. Consulting a monolingual or bilingual dictionary was the second most used strategy, while the least used strategy was asking the teacher to discover the meaning of the unknown words. Participants in this study reported that they prefer memory strategies over cognitive strategies. Moreover, they said that the accessibility of internet learning tools has contributed to increasing their vocabulary size and lexical knowledge.